A reforma educacional paulista dos anos de 1990: crítica aos modelos de análise - Oliveira, Juarez Bernardino de (2017)
We have investigated the pattern of analysis from São Paulo's educational reform in the 1990s, present in the academic production of the Postgraduate programs of the State of São Paulo. The objectives were: a) to identify the research guiding assumptions (thesis and dissertations), b) to analyze the existence of a predominant explanatory model on the subject, c) to examine the key categories defined to support the prevailing thesis that transformations in the educational policy and school administration in the 1990s in São Paulo were consequences of neoliberalism and managerialism and d) to analyze aspects neglected or exploited in a tangential way based on such a preponderant model. Horkheimer's (critically defined in 1937 in his article Traditional theory and critical theory), and the category of technological rationality, by Herbert Marcuse, were used as theoretical frameworks for the analysis. Twenty-four essays (thesis and dissertations) were selected between 1999 and 2013 in the universities located in São Paulo, which maintain Master and Doctoral programs in the Educational area. The hypothesis explored in the analysis was one in which the adherence of the governors to the patterns of educational policy and school management, defended in documents by international institutions, such as the World Bank, could only be clarified when considering the power of technological rationality as a guidance to the social relations in the capitalist society, and that the decisions of these governors and their programs were not merely the expression of rational individualities or specific political interests but above all the making of the "civilizing" march of capital which converted the objectives of enlarged reproduction due to the fact that it belongs to the contemporary world, invading all areas of social life, including education. It was concluded that a pattern of analysis prevailed in the academic production that neglected the elements of continuity and consensus of the educational policy of São Paulo, privileged the use of explanatory categories that referred to the field of small politics, as well as reducing the reform essentially to the condition of a political program and, this way, he elaborated an explanatory pattern that did not reconstitute the complex of determinations capable of clarifying the real movement of the educational policies and of education itself